Effects of games in STEM education: a meta-analysis on the moderating role of student background characteristics. Issue 1 (2nd January 2023) - Arztmann, Michaela; Hornstra, Lisette; Jeuring, Johan; Kester, Liesbeth
ABSTRACT: Game-based learning has proven to be effective and is widely used in science education, but usually the heterogeneity of the student population is being overlooked. To examine the differential effects of game interventions in STEM (Science, Technology, Engineering and Mathematics) related subjects on diverse student groups, a meta-analysis has been conducted that included 39 studies that compared game-based learning interventions with traditional classrooms in primary and early secondary education. We found moderate positive effects on cognition (g = .67), motivation (g = .51), and behaviour (g = .93). Additionally, substantial heterogeneity between studies was found. Moderator analyses indicated that primary school students achieve higher learning outcomes and experience game interventions as more motivating than secondary school students, whereas gender did not have any moderating effect. There were too few studies reporting information on the remaining moderators (socioeconomic status, migration background, and special educational needs) to include them in a multiple meta-regression model. Therefore, we assessed their role by separate moderator analyses, but these results need to be interpreted with caution. Additional descriptive analyses suggested that game-based learning may be less beneficial for students with low socioeconomic status compared to students with high socioeconomic status.